The impact of characteristics of online fan community and fans on loyalty to stars and the communities - Kim, Jonghun; Kang, Mincheol; Kim, Kimin (Journal of Theoretical and Applied Information Technology, 2019)
This study seeks to enhance understanding of online fan communities. We examined how online fan communities and their members affect loyalty to stars and the communities. We also examined how social and psychological factors such as social presence and identification mediate those impacts. By surveying online fans of Korean Wave Stars, we found that, among the online fan community characteristics, social connectedness, self-disclosure and deep profiling affect social presence, and, among the fan characteristics, self-focused attention and empathy affect social presence. We also found that social presence affects online fan community identification and star identification, which in turn affect online fan community loyalty and star loyalty. Moreover, star identification is found to transit to online fan community identification while star loyalty transited to online fan community loyalty. These findings provide significant theoretical and practical implications for the entertainment and media industries by adding to scant research on online fan communities.
Keywords: Identification; Korean wave stars; Loyalty; Online fan community; Social presence